The Women's Convention (Cedaw) and The Islamic Family Law (Federal Territories) ACT 1984: Constructing Harmonisation on Gender Equality - Nurulbahiah Binti Awang (Universiti Sains Islam Malaysia, 2024)
Matric :4130172 (FSU)